Perilaku Memilih Masyarakat pada Pilkada Klaten 2020, Ulasan Kemenangan Pasangan Sri Mulyani - Yoga Hardaya - Tedi Gunawan (Syntax Corporation Indonesia, 2023)
This research discusses the voting behavior of the people of Klaten in the 2020 local election in relation to the victory of the pair Sri Mulyani and Yoga Hardaya (MULYO). The purpose of this study is to identify the factors influencing voters in casting their votes for Sri Mulyani and Yoga Hardaya in the 2020 Klaten regional head election. The focus of this research was conducted in the Trucuk District as it has the largest Permanent Voter List (DPT) in Klaten. This study uses a mixed, quantitative-qualitative method. The quantitative approach was conducted with a survey research method on 397 people. The data analysis method used is multiple linear regression analysis. As for the qualitative approach, the researchers conducted in-depth interviews with several informants encountered. The results show that the voting behavior of the Klaten community is influenced by some factors, such as; Sociological, Psychological, Rational Choice, thus leading to the victory of the MULYO pair. The psychological factor becomes the dominant factor in determining choice by considering the prominence and party identification towards PDIP with a coefficient of 0.029. Meanwhile, the rational choice factor has a small influence on the selection of the regent candidate.